2018
DOI: 10.1097/ccm.0000000000003004
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Administration of Antibiotics and Fluids in the Treatment of Sepsis: A Murine Trial*

Abstract: We conclude that antibiotic therapy is highly time sensitive, and efforts should be made to deliver this critical therapy as early as possible in sepsis, perhaps extending into the first point of medical contact outside the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Due to the semi-quantitative and subjective nature of all three scoring systems, we monitored body temperature as an objective vital sign: our data show that temperature decreases over time in a sepsis severity-dependent manner and that reduced body temperature is a robust predictor of death in the CLP mouse model of sepsis—a novel and important finding. Recent studies by Lewis et al have shown that body temperature tracking with an implanted wireless biotelemetry device is useful for monitoring the physiologic response to antibiotic treatment and fluid resuscitation in murine sepsis [ 25 ], which is consistent with our findings that body temperature can be used to monitor disease severity in CLP sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the semi-quantitative and subjective nature of all three scoring systems, we monitored body temperature as an objective vital sign: our data show that temperature decreases over time in a sepsis severity-dependent manner and that reduced body temperature is a robust predictor of death in the CLP mouse model of sepsis—a novel and important finding. Recent studies by Lewis et al have shown that body temperature tracking with an implanted wireless biotelemetry device is useful for monitoring the physiologic response to antibiotic treatment and fluid resuscitation in murine sepsis [ 25 ], which is consistent with our findings that body temperature can be used to monitor disease severity in CLP sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…A 1-cm ligation, 21-gauge double puncture model of cecal ligation and puncture (CLP) under anesthesia was performed as previously described [16]. At the time of CLP, an HD-X11 wireless biotelemetry device (Data Sciences International, St. Paul, MN) capable of continuously measuring heart rate, core temperature, and activity was implanted into the peritoneal cavity in accordance with manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Latent class-based methods are applied in patients with acute respiratory distress syndrome (ARDS) to identify subphenotypes that are predictive of response to fluid management strategies [15]. We sought to capitalize on a recent murine randomized trial of prompt vs. delayed antibiotics and fluids enhanced by biotelemetry monitoring [16, 17] and use latent class methods to (i) identify murine sepsis phenotypes prior to overt, physiologic deterioration, (ii) explore their biologic profiles, and (iii) test their association with response to treatment. We hypothesized these data would provide “proof-of-concept” that drug-response phenotypes exist in a commonly used preclinical model of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…heart rate, body temperature, mobility) in mice (105107). Recently, Lewis et al (108) demonstrated a large-scale utility of biotelemetry monitoring for fluid resuscitation and antimicrobial treatment in CLP mice. In vivo wireless monitoring of cardiovascular endpoints has been successfully tested in pigs (109), dogs and non-human primates (110).…”
Section: Chapter 2: Humane Modelingmentioning
confidence: 99%